Prevalence and factors associated to back pain in adults from the northeast of São Paulo, Brazil: a population-based study - Alberto De Vitta; Marta Helena Souza De Conti; Nicoly Machado Maciel; Débora de Melo Trize; José Eduardo Corrente; Tânia Ruiz
Abstract Introduction: Back pain has become a serious public health problem. Objective: To determine the prevalence of back pain in a population-based sample of subjects over 20 years old living in the city of Bauru (São Paulo, Brazil) and to analyze the associations to variables- sociodemographic, ergonomic and lifestyle-related - and to morbidity. Methods: a cross-sectional study which evaluated 600 adults over 20 years old, both gender and living in the city. We used a structured protocol and the Nordic questionnaire. Also, we developed a descriptive analysis, bivariate and multivariate by binary logistic regression. Results: The prevalence of back pain was of 50.3% (CI 46.3 to 54.3), since 42.3% (CI 36.9 to 48.0) in men and 57.6% (CI 51.9 to 63.0) in women, with statistical significant difference (p = 0.001). Different variables remained in final models when assessed by gender. For male to be widowed and divorced and smoking habits and, for women to be widowed and divorced, to work in seated position and to perform occupational activities that demand carrying and lifting weight. Conclusion: We verified high prevalence in back pain in the population of Bauru and high association to widowed/divorced in both gender, with women performing occupational activities usually or always in seated position, those who carry or lift weight in work and men who smoke.